THE STUDY OF ELECTROPHYSIOLOGICAL MECHANISM OF PATHOLOGICAL SYSTEM REGRESSION AMONG THE PATIENTS WITH EPILEPSY BY THE METHOD OF SPECTRAL-COHERENCE ANALYSIS AND THE METHOD OF DIPOLE SOURCES - L. N. Nerobkova; Yu. B. Filatova; T. A. Voronina; G. G. Avakyan; E. A. Chromich; I. O. Gaydukov; G. N. Avakyan (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: the comparative analysis of bioelectric activity of a brain of patients with epilepsy before and after treatment by topiromate defined character of changes in a spectrum of EEG capacity and coherency, and also revealed communication between these indicators and degree of correction of clinical infringements. In our researches it is shown that at patients with positive clinical dynamics after topiromate application normalisation of the spatial organization of biopotentials is observed. The coherent analysis of narrow-band frequency components of oscillar activity of brain with the step of 1 Hz had revealed statistically significant changes of coherence in narrow ranges of frequencies. The direction of these changes and their pattern (inside- and/or interhemispheric communications) are connected with character of clinical changes. The analysis of dominating type of paroxysmal activity by the method of equivalent dipoles has shown that changes of character of the pathological activity, observed during therapy, is accompanied by changes of sources of its generation.